Industrial policy and features of industrial development in countries belonging to integration associations – the European Union and the Customs Union - Mykola Kyzym; Viktoria Khaustova (ACTA INNOVATIONS, 2016)
The article investigates the features of industrial development in countries belonging to integration associations — the European Union and the Customs Union, as well as the policy to support industrial development carried out in them, its targets, mechanisms and instruments. The study is based on analyzing the input-output tables for 38 countries, covering the period of 1995–2011. There have been analyzed: the dynamics of global production, growth rate of output and structure of industrial products in EU and CU countries, share of industry in the economy, growth rate of output and structure of industrial exports, export orientation of industrial production, growth rate of the internal market capacity and consumption structure of industrial products, growth rate of GDP of high-tech industries and share of high-tech industries in industrial GDP. There have been ranked: 20 EU and CU member countries — the largest manufacturers of industrial products, largest exporters and importers of industrial products, 20 countries leading in capacity of the internal market for industrial products, 20 EU and CU member countries with the highest level of import dependence of the internal market for industrial products, 20 EU and CU member countries leading in terms of GDP of high- tech industries. Basic features of the industrial policy in European Union countries as well as in CU member countries have been studied, their differences and weaknesses defined.